Pengaruh Pelatihan Dan Audit Sumber Daya Manusia Terhadap Produktivitas Kerja Karyawan pada PT. Sushi Tei Indonesia Cabang Gandaria City - Moh Faisal Muttaqin; Aden Prawiro Sudarso (Journal MISSY (Management and Business Strategy), 2020)
This study aims to determine the effect of HR training and audits on employee work productivity either partially or simultaneously at PT. Sushi Tei Indonesia, Gandaria City Branch. The analysis method used in this research is validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, t test and f test. The population in this study were employees of PT. Sushi Tei Indonesia, Gandaria City Branch. Using a saturated sample of 91 respondents. The results of this study based on the coefficient of determination show that HR training and auditing have contributed to employee work productivity by 36.9% while the remaining 63.10% are other variables not examined. The results showed the multiple linear regression equation Y = 22,750 + 0.139 (X1) + 0.445 (X2), meaning that even is a positive influence between (X1) and (X2) variables, employees still have a work productivity level of 22,750. The results showed that partially the training variable did not have a significant effect on employee work productivity by showing the results of the test tcount = 1.023 while ttable = 1.98729 (tcount <ttable) with a significance level of 0.309. partially the HR audit variable has a significant effect on employee work productivity by showing the results of tcount = 3.144 while ttable = 1.98729 (tcount> ttable) with a significance level of 0.002. The results of testing the simultaneous effect of independent variables on the dependent variable obtained the value of Fcount = 22.712> Ftable value = 3.10, so that H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence between training and HR audits on the work productivity of the employees of PT. Sushi Tei Indonesia, Gandaria City Branch.